Completely degradable PBAT composite material and preparation method thereof

By adding treated hemp fibers and hyperbranched unsaturated resin to the PBAT resin, a completely degraded composite material with high tensile and impact strength was prepared, which solved the problem of insufficient mechanical properties of PBAT materials and expanded its application range.

CN119220060APending Publication Date: 2024-12-31HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310773809.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-28
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The tensile strength and impact strength of PBAT materials limit their application in industry or life.

Method used

The treated hemp fiber is added to the PBAT resin and the hyperbranched unsaturated resin is used as the dispersant. The fully degradable PBAT composite material is prepared through the twin-screw extrusion mechanism to improve its mechanical properties.

Benefits of technology

The tensile strength and notch impact strength of PBAT composite materials have been significantly improved, making them suitable for packaging materials, catering utensils, sanitary products, mulch films, automobiles and medical fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004308704850000021
    Figure BDA0004308704850000021
  • Figure BDA0004308704850000071
    Figure BDA0004308704850000071
  • Figure BDA0004308704850000081
    Figure BDA0004308704850000081
Patent Text Reader

Abstract

The invention discloses a completely degradable PBAT composite material and a preparation method thereof. The completely degradable PBAT composite material is prepared from the following components in parts by weight: 60-100 parts of PBAT, 10-60 parts of fibrilia, 1-5 parts of a dispersing agent and 0.1-2 parts of an antioxidant. The dispersing agent is hyperbranched unsaturated resin. According to the invention, the treated jute fibers are added into the PBAT resin, the hyperbranched unsaturated resin can be well subjected to interface chemical application with surface groups of the jute fibers, and the hyperbranched unsaturated resin is well compatible with PBAT matrix resin, so that the jute fibers can be well dispersed in a resin matrix during melt extrusion; therefore, the tensile strength and notch impact strength of the PBAT resin can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer material modification, and in particular relates to a completely degradable PBAT composite material and a preparation method thereof. Background Art

[0002] Biodegradable plastics can be divided into bio-based biodegradable materials and petrochemical-based biodegradable materials according to their sources. PBAT, whose Chinese name is polybutylene terephthalate-adipate, is a petrochemical-based biodegradable plastic. It is one of the most active biodegradable materials in the current biodegradable plastic research and has the best market application. PBAT is a semi-crystalline polymer with a crystallization temperature of around 110°C, a melting point of around 130°C, and a density between 1.18g / ml and 1.3g / ml.

[0003] PBAT is a highly biodegradable polymer that completely breaks down when placed in a home compost, leaving no toxic residues. This makes it an excellent alternative to other non-biodegradable plastic materials. When PBAT is placed in a compost, it breaks down significantly faster than plastic. It takes approximately 60-120 days for PBAT to break down in an ideal composting environment, while plastics can take over 400 years. PBAT also does not release any toxic gases into the environment when it breaks down, and does not leave behind microplastics, making it a fully biodegradable polymer.

[0004] However, the tensile strength of PBAT is very low, especially the impact strength is not ideal, which limits its application in industry or life. Summary of the invention

[0005] In view of the defects of the prior art, an object of the present invention is to provide a PBAT composite material with excellent comprehensive mechanical properties and can be completely degraded; another object of the present invention is to provide a method for preparing the above-mentioned completely degradable PBAT composite material.

[0006] The technical solution of the present invention is as follows:

[0007] A completely degradable PBAT composite material is made from the following raw materials in parts by weight:

[0008]

[0009] The dispersant is a hyperbranched unsaturated resin.

[0010] The hyperbranched unsaturated resin is an unsaturated resin prepolymer with aromatic polyester as the skeleton, and its hydroxyl value is less than 20 mg KOH / g and its acid value is 60-80 mg KOH / g.

[0011] The melting point of the PBAT is 110-120°C and the melt index is 2-30g / 10min (190°C, 2.16kg);

[0012] The hemp fiber is selected from at least one of flax fiber, jute fiber, pure hemp fiber, hemp fiber, ramie fiber and kenaf fiber.

[0013] The fiber count is 10-80S.

[0014] The antioxidant is selected from at least one of hindered amine antioxidants, hindered phenol antioxidants, thio antioxidants and phosphite antioxidants.

[0015] Furthermore, the antioxidant is preferably at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098 or antioxidant 168.

[0016] The present invention also discloses a method for preparing the completely degradable PBAT composite material, which comprises the following steps:

[0017] (1) Dry 10-60 parts of hemp fiber at 60-90°C for 1-12 hours. Take out and evenly spray 1-5 parts of dispersant on the surface;

[0018] (2) Weighing 60-100 parts of PBAT and 0.1-2 parts of antioxidant, adding them into a twin-screw extruder, and then feeding the hemp fiber treated in step (1) into the extruder through a fiber feeding port, extruding and granulating, to prepare a completely degradable PBAT composite material;

[0019] In a further embodiment, the temperatures of the barrel sections of the extruder are set to: zone 1 60-100°C, zone 2 100-120°C, zone 3 120-140°C, zone 4 130-150°C, zone 5 140-150°C, zone 6 140-150°C, and die head 140-150°C.

[0020] Compared with the prior art, the present invention has the following advantages and beneficial effects:

[0021] 1. The present invention adds treated hemp fiber to PBAT resin, which can significantly improve the tensile strength and notched impact strength of PBAT resin. Since hemp fiber easily absorbs water, it needs to be dried before processing, and after drying, it needs to be put into use immediately.

[0022] 2. The dispersant of the present invention is a hyperbranched unsaturated resin, such as HyPerU102, which has the characteristics of low viscosity, high molecular weight, and high activity, and can be well interfacially chemically applied with the surface groups of hemp fibers. The hyperbranched unsaturated resin is well compatible with the PBAT matrix resin, and can make the hemp fibers well dispersed in the resin matrix during melt extrusion.

[0023] 3. Since PBAT has a high degree of crystallinity and high viscosity during processing, adding hyperbranched unsaturated resin to it can greatly improve its processing performance.

[0024] 4. The PBAT composite material prepared by the present invention has completely degradable properties and can be used in packaging materials, tableware, sanitary products, ground films, automobiles, medical treatment, textiles and other fields. DETAILED DESCRIPTION

[0025] The present invention will be further described below with reference to the embodiments.

[0026] If not specifically stated, the various raw materials of the present invention can be obtained commercially or prepared according to conventional methods in the art. Unless otherwise defined or stated, all professional and scientific terms used herein have the same meaning as those familiar to those skilled in the art. In addition, any method and material similar or equivalent to the described content can be applied to the method of the present invention. Other aspects of the present invention are obvious to those skilled in the art due to the disclosure of this article. The present invention is further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.

[0027] In the following examples and comparative examples, unless otherwise specified, the specifications and sources of raw materials are as follows:

[0028] Hyperbranched unsaturated resin HyPerU102, hydroxyl-terminated hyperbranched polyester, and vinyl-terminated hyperbranched polyester are all supplied by Wuhan Hyperbranched Resin Co., Ltd.

[0029] The brand of PBAT is TS159, with a tensile strength of 21.5MPA and a simply supported beam notched impact strength of 17.3KJ / m2. The supplier is Shenzhen Juhong New Materials Co., Ltd.

[0030] The hemp fiber is flax fiber with a count of 40S, and the supplier is Shanghai Jiayu Textile Co., Ltd.

[0031] The suppliers of antioxidant 1010 and antioxidant 168 are both DuPont of the United States.

[0032] The supplier of silane coupling agent KH550 is Jinan Nochuang Chemical Co., Ltd.

[0033] The suppliers of dispersant ethylene bisstearamide and dispersant barium stearate are both Mitsui Chemicals (Shandong) Co., Ltd.

[0034] The compositions of the present invention are injection molded using ASTM standards.

[0035] The spline dimensions (length × width × thickness) are: tensile spline (dumbbell shape), 170 mm × 13 mm × 3.2 mm; notched impact spline, 127 mm × 13 mm × 3.2 mm, V-notch, notch depth of 1 / 5.

[0036] Tensile strength: tested according to ASTM D638, tensile speed is 5mm / min.

[0037] Charpy notched impact strength: tested according to ASTM D6110.

[0038] Example 1

[0039] (1) 55 parts of hemp fibers were dried at 80° C. for 2 h, and then 4 parts of hyperbranched unsaturated resin HyPerU102 were evenly sprayed on the surface of the fibers;

[0040] (2) Weighing 100 parts of PBAT and 0.5 parts of antioxidant 1010, adding them into a twin-screw extruder, and then feeding the hemp fiber treated in step (1) into the extruder through the fiber feeding port, extruding and granulating, to prepare a completely degradable PBAT composite material;

[0041] The temperatures of the barrel sections of the extruder were set as follows: 60°C for zone 1, 100°C for zone 2, 120°C for zone 3, 130°C for zone 4, 140°C for zone 5, 150°C for zone 6, and 150°C for the die head.

[0042] Example 2

[0043] (1) Dry 15 parts of hemp fiber at 70°C for 5 hours. Take it out and evenly spray 1 part of hyperbranched unsaturated resin HyPerU102 on its surface.

[0044] (2) Weighing 60 parts of PBAT and 0.3 parts of antioxidant 1010, adding them into a twin-screw extruder, and then feeding the hemp fiber treated in step (1) into the extruder through the fiber feeding port, extruding and granulating, to prepare a completely degradable PBAT composite material;

[0045] The temperatures of the barrel sections of the extruder were set as follows: 80°C for zone 1, 100°C for zone 2, 120°C for zone 3, 130°C for zone 4, 140°C for zone 5, 140°C for zone 6, and 150°C for the die head.

[0046] Example 3

[0047] (1) Dry 30 parts of hemp fiber at 65°C for 10 hours. Take it out and evenly spray 2 parts of hyperbranched unsaturated resin HyPerU102 on its surface.

[0048] (2) Weigh 90 parts of PBAT, 0.4 parts of antioxidant 1010, and 0.4 parts of antioxidant 168, and add them into a twin-screw extruder, then add the hemp fiber treated in step (1) into the extruder through the fiber feeding port, extrude and granulate, and prepare a completely degradable PBAT composite material;

[0049] The temperatures of the barrel sections of the extruder were set as follows: zone 1 100°C, zone 2 120°C, zone 3 140°C, zone 4 150°C, zone 5 150°C, zone 6 150°C, and die head 150°C.

[0050] Example 4

[0051] (1) Dry 45 parts of ramie fibers at 80°C for 2 hours. Take them out and evenly spray 2 parts of hyperbranched unsaturated resin HyPerU102 on their surface.

[0052] (2) Weighing 100 parts of PBAT, 0.3 parts of antioxidant 1010, and 0.3 parts of antioxidant 168, adding them into a twin-screw extruder, and then adding the hemp fiber treated in step (1) into the extruder through the fiber feeding port, extruding and granulating, to prepare a completely degradable PBAT composite material;

[0053] The temperatures of the barrel sections of the extruder were set as follows: 60°C for zone 1, 100°C for zone 2, 120°C for zone 3, 130°C for zone 4, 140°C for zone 5, 140°C for zone 6, and 150°C for the die head.

[0054] Comparative Example 1

[0055] 100 parts of PBAT, 0.3 parts of antioxidant 1010, and 0.3 parts of antioxidant 168 were weighed and added into a twin-screw extruder, and then 45 parts of hemp fiber (dried at 80° C. for 2 h) were added into the extruder through the fiber feeding port, and extruded and granulated to prepare a completely degradable PBAT composite material;

[0056] The temperatures of the barrel sections of the extruder were set as follows: 60°C for zone 1, 100°C for zone 2, 120°C for zone 3, 130°C for zone 4, 140°C for zone 5, 140°C for zone 6, and 150°C for the die head.

[0057] Comparative Example 2

[0058] Weigh 100 parts of PBAT, 2 parts of hyperbranched unsaturated resin HyPerU102, 0.3 parts of antioxidant 1010, and 0.3 parts of antioxidant 168, add them into a twin-screw extruder, then add 45 parts of hemp fiber (dried at 80°C for 2h) into the extruder through the fiber feeding port, extrude and granulate, and prepare a completely degradable PBAT composite material;

[0059] The temperatures of the barrel sections of the extruder were set as follows: 60°C for zone 1, 100°C for zone 2, 120°C for zone 3, 130°C for zone 4, 140°C for zone 5, 140°C for zone 6, and 150°C for the die head.

[0060] Comparative Example 3

[0061] (1) Dry 45 parts of hemp fiber at 80°C for 2 hours. Take it out and evenly spray 2 parts of dispersant KH550 on its surface.

[0062] (2) Weighing 100 parts of PBAT, 0.3 parts of antioxidant 1010, and 0.3 parts of antioxidant 168, adding them into a twin-screw extruder, and then adding the hemp fiber treated in step (1) into the extruder through the fiber feeding port, extruding and granulating, to prepare a completely degradable PBAT composite material;

[0063] The temperatures of the barrel sections of the extruder were set as follows: 60°C for zone 1, 100°C for zone 2, 120°C for zone 3, 130°C for zone 4, 140°C for zone 5, 140°C for zone 6, and 150°C for the die head.

[0064] Comparative Example 4

[0065] Weigh 100 parts of PBAT, 2 parts of dispersant ethylene bisstearamide, 0.3 parts of antioxidant 1010, and 0.3 parts of antioxidant 168, add them into a twin-screw extruder, then add 45 parts of hemp fiber (dried at 80°C for 2h) into the extruder through the fiber feeding port, extrude and granulate, and prepare a completely degradable PBAT composite material;

[0066] The temperatures of the barrel sections of the extruder were set as follows: 60°C for zone 1, 100°C for zone 2, 120°C for zone 3, 130°C for zone 4, 140°C for zone 5, 140°C for zone 6, and 150°C for the die head.

[0067] Comparative Example 5

[0068] 100 parts of PBAT, 2 parts of dispersant barium stearate, 0.3 parts of antioxidant 1010, and 0.3 parts of antioxidant 168 were weighed and added into a twin-screw extruder, and then 45 parts of hemp fiber (dried at 80° C. for 2 h) were added into the extruder through the fiber feeding port, extruded and granulated to prepare a completely degradable PBAT composite material;

[0069] The temperatures of the barrel sections of the extruder were set as follows: 60°C for zone 1, 100°C for zone 2, 120°C for zone 3, 130°C for zone 4, 140°C for zone 5, 140°C for zone 6, and 150°C for the die head.

[0070] Comparative Example 6

[0071] 100 parts of PBAT, 2 parts of terminal hydroxyl hyperbranched polyester, 0.3 parts of antioxidant 1010, and 0.3 parts of antioxidant 168 were weighed and added into a twin-screw extruder, and then 45 parts of hemp fiber (dried at 80° C. for 2 h) were added into the extruder through the fiber feeding port, and extruded and granulated to prepare a completely degradable PBAT composite material;

[0072] The temperatures of the barrel sections of the extruder were set as follows: 60°C for zone 1, 100°C for zone 2, 120°C for zone 3, 130°C for zone 4, 140°C for zone 5, 140°C for zone 6, and 150°C for the die head.

[0073] Comparative Example 7

[0074] (1) Dry 45 parts of ramie fibers at 80°C for 2 hours. Take them out and evenly spray 2 parts of vinyl-terminated hyperbranched polyester on their surface.

[0075] (2) Weighing 100 parts of PBAT, 0.3 parts of antioxidant 1010, and 0.3 parts of antioxidant 168, adding them into a twin-screw extruder, and then adding the hemp fiber treated in step (1) into the extruder through the fiber feeding port, extruding and granulating, to prepare a completely degradable PBAT composite material;

[0076] The temperatures of the barrel sections of the extruder were set as follows: 60°C for zone 1, 100°C for zone 2, 120°C for zone 3, 130°C for zone 4, 140°C for zone 5, 140°C for zone 6, and 150°C for the die head.

[0077] Table 1 Mechanical properties of materials

[0078]

[0079]

[0080] According to the above embodiments, comparative examples and performance test data, it can be seen that the dispersant in the present application is a hyperbranched unsaturated resin HyPerU102, which has the characteristics of low viscosity, high molecular weight and high activity, and can better undergo interfacial chemical application with the surface groups of hemp fibers.

[0081] The hyperbranched unsaturated resin HyPerU102 has good compatibility with the PBAT matrix resin, so during melt extrusion, the hemp fiber can be better dispersed in the resin matrix, thereby improving the mechanical properties of the material.

[0082] In Comparative Example 2, the hemp fiber was not treated, that is, the hyperbranched unsaturated resin HyPerU102 was not sprayed on the hemp fiber for treatment. Compared with Example 4, although the added components and amounts were the same, the tensile strength and simply supported beam notched impact strength of the final composite material were still significantly lower than those of Example 4, indicating that surface treatment of hemp fiber with the hyperbranched unsaturated resin HyPerU102 can significantly improve the tensile strength and notched impact strength of the PBAT resin.

[0083] Although silane coupling agent KH550, dispersant ethylene bisstearamide, dispersant barium stearate, terminal hydroxyl hyperbranched polyester, and terminal vinyl hyperbranched polyester were added to Comparative Examples 3-7, the dispersion effect in the material was poor, and the tensile strength and simply supported beam notched impact strength of the prepared PBAT composite material were significantly lower than those in Example 4.

[0084] The present invention adds treated hemp fiber to PBAT resin, which can significantly improve the tensile strength and notched impact strength of PBAT resin. The PBAT composition of the present invention has a completely degradable property and can be applied to packaging materials, tableware, sanitary products, ground film, automobiles, medical treatment, textiles and other fields.

[0085] The above description of the embodiments is to facilitate the understanding and application of the present invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the embodiments herein, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. A completely degradable PBAT composite material, characterized in that: It is prepared from the following components by weight: The dispersant is a hyperbranched unsaturated resin.

2. The PBAT composite material according to claim 1, characterized in that: The hyperbranched unsaturated resin refers to an unsaturated resin prepolymer with an aromatic polyester as a skeleton, and its hydroxyl value is less than 20 mg KOH / g and its acid value is 60-80 mg KOH / g.

3. The PBAT composite material according to claim 1, characterized in that: The melting point of the PBAT is 110-120° C., and the melt index is 2-30 g / 10 min at 190° C. / 2.16 kg.

4. The PBAT composite material according to claim 1, characterized in that: The hemp fiber is selected from at least one of flax fiber, jute fiber, pure hemp fiber, hemp fiber, ramie fiber and kenaf fiber; wherein the fiber count is 10-80S.

5. The PBAT composite material according to claim 1, characterized in that: The antioxidant is selected from at least one of hindered amine antioxidants, hindered phenol antioxidants, thio antioxidants and phosphite antioxidants.

6. The PBAT composite material according to claim 5, characterized in that: The antioxidant is at least one of antioxidant 1010, antioxidant 1076, antioxidant 1098, and antioxidant 168.

7. The method for preparing the PBAT composite material according to claim 1, characterized in that: The following steps are involved: (1) After drying 10-60 parts of hemp fiber at 60-90° C. for 1-12 hours, 1-5 parts of a dispersant are evenly sprayed on the surface of the fiber; (2) Weigh 60-100 parts of PBAT and 0.1-2 parts of antioxidant, add them into a twin-screw extruder, then add the hemp fiber treated in step (1) into the extruder through the fiber feeding port, extrude and granulate, and prepare a completely degradable PBAT composite material.

8. The preparation method according to claim 7, characterized in that: The temperatures of the barrel sections of the extruder are respectively set to: 60-100°C in zone 1, 100-120°C in zone 2, 120-140°C in zone 3, 130-150°C in zone 4, 140-150°C in zone 5, 140-150°C in zone 6, and 140-150°C in the die head.